Current Developments in the Chemical Upcycling of Waste Plastics Using Alternative Energy Sources. Issue 19 (17th June 2021) - Karimi Estahbanati, M. R.; Kong, Xin Ying; Eslami, Ali; Soo, Han Sen
Abstract: The management of plastics waste is one of the most urgent and significant global problems now. Historically, waste plastics have been predominantly discarded, mechanically recycled, or incinerated for energy production. However, these approaches typically relied on thermal processes like conventional pyrolysis, which are energy‐intensive and unsustainable. In this Minireview, some of the latest advances and future trends in the chemical upcycling of waste plastics by photocatalytic, electrolytic, and microwave‐assisted pyrolysis processes are discussed as more environmentally friendly alternatives to conventional thermal reactions. We highlight how the transformation of different types of plastics waste by exploiting alternative energy sources can generate value‐added products such as fuels (H2 and other carbon‐containing small molecules), chemical feedstocks, and newly functionalized polymers, which can contribute to a more sustainable and circular economy. Abstract : Green upcycling : This Minireview highlights the state of the art in exploiting alternative energies via photocatalysis, electrolysis, and microwave‐assisted pyrolysis to chemically upcycle plastics waste into value‐added products such as H2, carbon‐neutral fuels, chemical feedstocks, and functionalized polymers. The advances and challenges for each technology are reviewed to give insights into future trends for more sustainable plastics waste management.